"Duet‐Insurance" Eutectic Electrolytes for Zinc‐Ion Capacitor Pouch Cells. (4th January 2023) - Lu, Xuejun; Tao, Li; Qu, Keqi; Amardeep, Amardeep; Liu, Jian
Abstract: Eutectic electrolytes are emerging to be explored to meet the high demand for aqueous zinc‐ion capacitors (AZICs) due to their high electrochemical stability and environmental‐friendly feature. Notably, a large‐scale requirement for a practical AZIC has been addressed to balance decent performance and increase package size. Thus, a "duet‐insurance" eutectic electrolyte (DIEE) is proposed by introducing successively heavy water (D2 O) and dimethyl sulfoxide in an aqueous chaotropic Zn salt solution, which hindered the severe irreversibility of Zn anodes compared to that lacking this dual‐solvent protection. For example, the optimal DIEE delivered a high capacitance of 352.9 F g −1 at 0.5 A g −1 and excellent capacitance retention of ≈100% over 30, 000 cycles at 2 A g −1 implementing in pouch cells and showing the ability to operate at a low temperature. Besides, experimental (e.g., nuclear magnetic resonance spectroscopy, Raman spectroscopy, electric double‐layer capacitance, etc.) and theoretical techniques (e.g., molecular dynamics simulation, density functional theory) illustrate the vital presence of contact ion pairs and aggregates ion species. Ultimately, this efficient DIEE system employing "duet‐insurance" protections provides a promising direction for designing novel eutectic electrolytes for AZICs chemistries. Abstract : A "duet‐insurance" eutectic electrolyte (DIEE) is proposed where the duplicate solvents of heavy water (D2 O) and dimethyl sulfoxide coordinated well with water‐based eutectic electrolytes. DIEEs delivered excellent Zn‐ion capacitor performance with long‐term cycling stability in pouch cell assembly benefiting from dual‐protection effects.